Z-Accounting : Menciptakan Generasi Baru Akuntan Profesional Dalam Era Revolusi Industri 4.0 - Pratama, Bagas Brian (Jurnal Pendidikan Akuntansi (JPAK), 2024)
The Industrial Revolution 4.0 changed society's physical and psychological needs, including economic and business. In this condition, accounting education to produce future generations of accountants must provide appropriate learning to respond to the changes that occur. Moreover, changes in society in this era have also given birth to a new generation with unique and different characteristics than previous generations. Therefore, this research will analyze and design an accounting education model appropriate to the development of the Industrial Revolution 4.0 era and the character of future generations of students. The research method uses qualitative data collection techniques through interviews and documentation. The interviews were with accounting practitioners from public institutions, corporations, and professionals. Four stages must be carried out, including formulating research objectives clearly and objectively, identifying informant sources and literature sources appropriate to the research topic, conducting interviews for information, extracting data from literature sources, and finally, analyzing and concluding the research results. The research results show that changes in accounting education strategies are needed to prepare professional accountants for the future. The first is that accounting education must be technology-based to accommodate the digital abilities of the millennial generation. Second, accounting education must prepare a learning model that suits the character of the millennial generation. The success of these two strategies will create a new generation of professional accountants in the future who have strong personalities, are idealistic and self-confident, are team-oriented, creative and innovative, and have a high ability to use digital technology.